2012
DOI: 10.1089/lap.2012.0042
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Thoracoscopic Thymectomy for Treating Myasthenia Gravis in Children

Abstract: Robotic-assisted thoracoscopic thymectomy is a safe and effective operation for children with MG. Robotic assistance allows for articulating instruments, three-dimensional visualization, and minimal blood loss. These factors may allow for a more complete resection compared with a standard thoracoscopic thymectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…23 Because the most common indications for thymectomies are MG and thymomas, surgeons must be assured that robotic-assisted thymectomies can yield the same clinical improvements as other types of thymectomies. Thus, many series have confirmed that robotic-assisted thymectomy is a plausible treatment option for patients with MG. [24][25][26][27][28][29][30] Hartwich et al 30 showed that robotic-assisted thymectomy can improve symptoms in children with MG. Collectively, 82% to 92% of patients had improved symptoms of MG following robotic-assisted thymectomy, and the complete remission rate was as high as 28.5%.…”
Section: Thymectomymentioning
confidence: 99%
See 1 more Smart Citation
“…23 Because the most common indications for thymectomies are MG and thymomas, surgeons must be assured that robotic-assisted thymectomies can yield the same clinical improvements as other types of thymectomies. Thus, many series have confirmed that robotic-assisted thymectomy is a plausible treatment option for patients with MG. [24][25][26][27][28][29][30] Hartwich et al 30 showed that robotic-assisted thymectomy can improve symptoms in children with MG. Collectively, 82% to 92% of patients had improved symptoms of MG following robotic-assisted thymectomy, and the complete remission rate was as high as 28.5%.…”
Section: Thymectomymentioning
confidence: 99%
“…28,31,32,53 In addition, among study patients with myasthenia gravis undergoing thymectomy, those undergoing robotic-assisted thymectomy have similar rates of symptom improvement and cure compared with those undergoing other surgical modalities. [24][25][26][27][28][29][30] Despite these positive results for robotic-assisted surgery in the mediastinum, thymectomy is still the most published operation of all robotic-assisted mediastinal resections; as of 2012, approximately 3,500 cases have been registered with Intuitive Surgical. 54 In addition, median sternotomy is considered the gold standard approach for thymus gland removal -a fact that could be due to the perceived increased cost associated with robotic surgery.…”
Section: Posterior Mediastinummentioning
confidence: 99%
“…Long-term results after thymectomy for early-stage thymoma have also been excellent, with a 5-year survival rate of 90%, though longer-term data with regards to survival and recurrence (a relevant consideration in this fairly indolent disease) remains unknown (10). Robotic thymectomy in pediatric patients and in patients with larger tumors and tumors involving lung, pericardium, and phrenic nerve have also been performed safely (11,12). We view invasion into the mediastinal vessels as the only indication for routine conversion (or initial approach via sternotomy, if obvious).…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies have reported that robotassisted surgery is safe and feasible for pediatric patients. RATS has previously been described as part of a series of general pediatric surgeries or a series of various thoracic pathologies [22,23,26,27] , a series of pediatric cases of specific procedures such as thymectomy for myasthenia gravis [28,29] , tracheopexy for treatment of severe tracheomalacia [30] , or as pediatric case reports on esophageal leiomyoma and bronchogenic cyst [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the detailed non-systematic review of previous publications in PubMed on noncardiovascular thoracic pathology treated with robotic surgery in the pediatric population worldwide, currently, the number of children treated with this technology barely has reached 100 cases, and all related references with the theme are included [11,22,[26][27][28][29][30][31][32][33][34]36,39,44,45] .…”
Section: Congenital Diaphragm Abnormalities Including Eventration Anmentioning
confidence: 99%